Potential Hazards from Electrosurgery Plume Recommendations for Surgical Smoke Evacuation - Hoglan, Marlys (Operating Room Nurses Association of Canada Journal, 1995)
Most hospitals today are “non smoking” hospitals. Where is the one place in the hospital that smoking occurs on a daily basis and nobody objects? That’s right, the operating room, and who is breathing it? The perioperative nursing staff, anesthesia personnel, surgeons, and the patient. What you see in the OR every day is the steam and what you are breathing is the vaporized tissue. The cancer society took a long time to convince us that cigarette smoke caused lung cancer. Think about the years and years of research that went into their findings before they said “yes, we have proven it, cigarette smoking is hazardous to your health.” Per- haps research will eventually tell us that breathing electrosurgery (ES) smoke is also hazardous to our health.